2002
DOI: 10.1111/j.1530-0277.2002.tb02666.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of chronic alcohol consumption and exercise on the skeleton of adult male rats

Abstract: Chronic alcohol consumption significantly reduced bone formation. Exercise had no effect on the bone and did not attenuate any of the negative effects of alcohol. The results suggest that alcohol consumption weakens the skeleton and increases the incidence of endurance-exercise-related bone injuries. Thus, individuals who are participating in endurance exercise and consuming alcohol may be at greater risk for exercise-related skeletal injuries. Further investigation of the potential for alcohol to induce detri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 29 publications
3
8
1
Order By: Relevance
“…In another study, the extent of alcohol consumption in a group of 258 healthy men (aged 40-63) did not differentiate trabecular, cortical or total BMC values at the distal radius [15]. However, there are also several animal studies on alcohol and bone microarchitecture that corroborate our findings [30,31].…”
Section: Discussionsupporting
confidence: 82%
“…In another study, the extent of alcohol consumption in a group of 258 healthy men (aged 40-63) did not differentiate trabecular, cortical or total BMC values at the distal radius [15]. However, there are also several animal studies on alcohol and bone microarchitecture that corroborate our findings [30,31].…”
Section: Discussionsupporting
confidence: 82%
“…Adrenal gland weights normalized to tibia length were significantly greater in the females versus males and were not affected by exercise training in either sex. Training significantly reduced body weight in male but not female rats, which is consistent with previous evidence that male rats do not compensate for increased physical activity by increasing caloric intake (5,49). Training had no effect on normalized LV or adrenal weights in either sex (ANOVA) but led to a significant reduction in spleen weight in males, indicating that the training protocol may have elicited some systemic distress in male rats (42,50).…”
Section: Morphology Datasupporting
confidence: 88%
“…27 The reduction in human body weight during chronic alcohol consumption is associated with the fact that part of the daily diet calorie intake is provided by the alcoholic beverage; 27 however, this impact on weight is rarely observed in rats. 28 In the present study, the systemic effect of alcohol consumption observed by analysis of rat body weight showed that groups that consumed ethanol or carbohydrates gained weight. Similarly, Irie et al 12 , (2008) showed a weight gain in ethanol and isocaloric groups during the experimental period.…”
Section: Discussionsupporting
confidence: 51%